Baseline findings from a quasi-experimental study on educational interventions for high-risk obstetric clients in Nairobi County: Maternal healthcare utilization remains suboptimal in many low-resource - Osoro, Epony Nyakong`anyi; Tenambregen, Wanja Mwaura; Njoroge, Kezia (Journal of Surgery and Medicine, 2026)
Background/Aim: Maternal healthcare utilization among high-risk obstetric patients in dense urban settings, such as Nairobi, remains inconsistent despite ongoing national programs. This baseline study characterized knowledge, service utilization, cultural influences, and use of the Maternal and Child Health (MCH) handbook among high-risk women prior to an educational intervention. Methods: A cross-sectional baseline survey was conducted as the first phase of a larger quasi-experimental study (pre–post with intervention and control groups). A total of 205 high-risk pregnant patients (intervention, n = 145; control, n = 60) attending two Level 5 hospitals in Nairobi County participated in the survey. Structured interviewer-administered questionnaires were used to collect data on demographic characteristics, obstetric knowledge, antenatal care (ANC) and postnatal care service utilization, cultural beliefs, and acceptance of the MCH handbook. Descriptive statistics were applied to summarize the baseline status. Results: The participants were predominantly aged 25–34 years and had attained secondary or higher levels of education. Baseline knowledge scores were moderate (intervention: 53.18%; control: 51.77%), whereas adequate ANC attendance (≥4 visits) was notably low (intervention: 2.54%; control: 2.27%). Prenatal education was limited, with many respondents reporting minimal discussion of birth plans or postpartum support. Cultural factors, including fear of judgment, perceived disrespect, and reliance on traditional healers, were strongly associated with low service utilization. Although the MCH handbook was generally well received, routine use remained <50% in both groups. These patterns align with evidence from other urban and low- and middle-income country studies that link structural, informational, and cultural barriers to suboptimal maternal service uptake. Conclusion: Baseline data reveal significant gaps in knowledge, service utilization, and integration of the MCH handbook among high-risk obstetric patients in Nairobi County. The forthcoming educational intervention should be culturally tailored, strengthen provider–client communication, and incorporate practical MCH handbook training to improve service utilization and maternal outcomes.